Patient Satisfaction on Surgical Service Decision Time in Emergency Department of A Tertiary Hospital in Indonesia - Shabrina Adzania; Nucki Nursjamsi Hidajat; Elsa Pudji Setiawati (Althea Medical Journal, 2021)
Background: Patient satisfaction survey is essential for evaluating and developing plans to improve health services' quality. One of the emergency department service quality indicators is decision time. Overcrowding of the emergency room as a result of long decision time may cause dissatisfaction among patients. This study aimed to evaluate the satisfaction level of patients receiving surgical services and the correlation between the satisfaction level and  surgical service decision time.Methods: A cross-sectional descriptive analytical study was conducted from September to November 2019 at the emergency department of Dr. Hasan Sadikin General Hospital. The consecutive sampling method was applied and a total of 110 patients met the inclusion and exclusion criteria. Patient satisfaction was assessed using a validated questionnaire and data on decision time was obtained from the patient’s medical record. Spearman correlation test was used to analyze the data.Results: This study discovered that most of the respondents were satisfied with the service (92.7%) and that decision was mostly made in less than 2 hours (79.1%). A weak negative correlation (ρ = - 0.144), was identified between decision time and patient satisfaction, albeit insignificant (p = 0.067), with a confidence interval of 95% (α = 5%).Conclusion: This study suggested that there is no correlation between patient satisfaction and decision time. Thus, decision time is not the main factor that determines patient satisfaction.